(320) محاضرات في الاقتصادات الدولية(الجزء الاول) Lectures in International Economics – Part I - سمير طوبار (معهد التخطيط القومي, 2026)
يتناول هذا البحث دراسة إحصائية وميدانية حول قضايا العمالة والبطالة بين خريجي الشهادات المتوسطة (الثانوية وما يعادلها) في الجمهورية العربية المتحدة، حيث شملت العينة 612 مبحوثاً من مختلف المحافظات ، استعرضت الدراسة الخصائص الديموغرافية والاجتماعية للمبحوثين، مشيرةً إلى أن متوسط الدخل الشهري حينها كان يقارب 14 جنيهاً، وهو ما اعتبره البحث سبباً رئيسياً لارتفاع نسبة غير المتزوجين بينهم والتي تجاوزت 64% كما كشف البحث عن فجوة في المهن بين الأبناء وآبائهم، مع ميل الخريجين للعمل "كمستخدمين" (موظفين) بدلاً من الأعمال الحرة بسبب طبيعة التعليم الذي لم يكن يؤهلهم للمشاريع الخاصة على صعيد التعليم والتدريب، أظهرت النتائج أن الميل الشخصي ورأي الأسرة كانا المحركين الأساسيين لاختيار نوع الدراسة الثانوية ، وبالرغم من أن أكثر من 73% من المبحوثين تلقوا تدريباً عملياً أو فنياً، إلا أن البحث رصد حالة من عدم الرضا الوظيفي لدى شريحة منهم، حيث أعرب 23.4% عن رغبتهم في الحصول على نوع آخر من التعليم، كما لفتت الدراسة إلى أن الاستقرار الوظيفي ارتبط بشكل وثيق بمدى رضاء الخريج عن دراسته وتوافقها مع طبيعة عمله، في حين فضل البعض تحسين وضعهم الاقتصادي عبر قبول الأعمال اليدوية. This research presents a statistical and field study on employment and unemployment issues among graduates of intermediate certificates (secondary and equivalent) in the United Arab Republic. The sample included 612 respondents from various governorates. The study reviewed the demographic and social characteristics of the respondents, noting that the average monthly income at the time was approximately 14 Egyptian pounds. The research considered this a primary reason for the high percentage of unmarried individuals among them, exceeding 64%. The research also revealed a gap in professions between children and their parents, with graduates tending to work as "employees" rather than pursuing self-employment due to the nature of their education, which did not prepare them for private projects. Regarding education and training, the results showed that personal inclination and family opinion were the main drivers in choosing the type of secondary education. Although more than 73% of the respondents received practical or technical training, the research observed job dissatisfaction among a segment of them, with 23.4% expressing a desire to obtain another type of education. The study also indicated that job stability was closely linked to The degree of satisfaction of the graduate with his studies and their compatibility with the nature of his work, while some preferred to improve their economic situation by accepting manual labor.